Students learn the technical process of the banana plant and its post-harvest process. - Medina, Reina (Revista Universidad de Guayaquil, 2009)
The banana activity in Ecuador for the past forty years has had a significant weight in the development of the country, both from an economic and social perspective; due to its important contribution to the GDP and the sources of employment it generates.According to information from the Ministry of Agriculture and Fisheries (MAGAP), the national area dedicated to banana production is 209,275 hectares, mostly located in the provinces of El Oro, Guayas, and Los Ríos